(untitled) (The Batuk, 2019)
This study attempted to measure factors of brand image and television purchase in Kathmandu City. Descriptive and causal research design was used. Primary cross-section data were collected. Structured questionnaires were administered and 200 data were obtained. Judgmental sample technique was applied. Structural Equation Modeling (SEM) tool was used to validate the model and testing causal relationships among exogenous and endogenous constructs. It was found consumer experience and after sales service were the important factors for creating brand image in the television markets. Brand image influenced television buying behavior. But celebrity endorsement and country of origin had no influence on building brand image.